The Dolphin Crossing - "Walsh, Jill Paton" (Puffin Books: LOndon, 1995)
Pat and his friend John know the risks they face when taking a boat across the Channel in the spring of 1940. But they also knew they had to do something to help the British soldiers stranded in Dunkirk.
Keywords: Children's stories Fiction